Thickness optimization of a geometrically non-linear arch at a limit point - Aubert, Pierre (Zielona Góra: Uniwersytet Zielonogórski)
An optimization method for geometrically non-linear mechanical structures based on a sensitivity gradient is proposed. This gradient is computed by using an adjoint state equation and the structure is analysed by means of a total Lagrangian formulation. This classical method is well-understood for regular cases, but standard equations (see e.g. Rousselet et al., 1995) have to be modified for the limit-point case.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka